Dual intercalation of inorganics–organics for synergistically tuning the layer spacing of V2O5·nH2O to boost Zn2+ storage for aqueous zinc-ion batteries. Issue 24 (9th June 2022) - Feng, Ziyi; Zhang, Yifu; Zhao, Yunfeng; Sun, Jingjing; Liu, Yanyan; Jiang, Hanmei; Cui, Miao; Hu, Tao; Meng, Changgong
Abstract : A "co-intercalation mechanism" is proposed in which magnesium ions and polyaniline are simultaneously inserted into the layers of hydrated V2 O5 as the cathode material for ARZIBs. Abstract : Possessing a 2D zinc-ion transport channel, layered vanadium oxides have become good candidates as cathode materials for aqueous rechargeable zinc-ion batteries (ARZIBs). Tuning the lamellar structure of vanadium oxides to enhance their zinc-ion storage is a great challenge. In the present study, we proposed and investigated a "co-intercalation mechanism" in which Mg 2+ and polyaniline (PANI) were simultaneously intercalated into the layers of hydrated V2 O5 (MgVOH/PANI) by a one-step hydrothermal method. Inorganic–organic co-intercalation could tune the layer spacing of VOH, and this combination played a synergistic role in enhancing the zinc-ion storage in MgVOH/PANI. It showed an extremely large layer spacing of 14.2 Å, specific capacity of up to 412 mA h g −1 at 0.1 A g −1, and the capacity retention rate could reach 98% after 1000 cycles. PANI itself has a zinc-storage capacity, and Mg 2+ intercalated with PANI can improve the conductivity of the material and enhance its stability. Further first-principles calculations clearly revealed the structural changes and improved electrochemical performance of vanadium oxides. This method of inorganic and organic co-regulation of the VOH structure opens a new strategy for tuning the lamellar structure of layered materials to boost their electrochemical performances.